A Computational Survey of Layered Mixed Phases Mn1−Xnixps3 for Water Splitting: Modulation of the Band Gap and the Oxygen Evolution Reaction - Aliaga-Vidal, C; Aliaga-Vidal, C (Elsevier Ltd, 2025)
In pursuing sustainable energy solutions, developing efficient (photo)catalysts for water splitting utilizing low-cost and abundant materials is essential for advancing green hydrogen production technologies. This computational study investigates the potential of lamellar (2D) thiophosphate mixed phases [Figure presented] as a catalyst for the oxygen evolution reaction (OER) in water splitting processes. Employing density functional theory simulations that account for spin–orbit coupling, we demonstrate that incorporating Ni cations significantly reduces the bandgap by approximately 0.7 eV while optimizing the valence band for effective water photo-oxidation. By analyzing free energy pathways for the adsorption of intermediate species during the OER, we identify the formation of [Figure presented] as the crucial step influencing the overpotential in these materials. Notably, the incorporation of Ni cations reduces the overpotential from 1.41 eV in MnPS3 to 1.12 eV in the [Figure presented] mixed phase. Furthermore, when Ni cations are introduced as adatoms on the surface of MnPS3, the overpotential decreases to an impressive 0.29 eV, which is comparable with state-of-the-art catalysts like IrO2. Overall, this study provides valuable computational insights into the potential of 2D [Figure presented] materials as promising alternative catalysts for the OER. © 2024 Hydrogen Energy Publications LLC